2021
DOI: 10.3390/toxics9090207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Neurotoxicity Associated with Exposure to the Herbicide Atrazine

Abstract: Atrazine is an herbicide commonly used on crops to prevent broadleaf weeds. Atrazine is an endocrine-disrupting chemical mainly targeting the neuroendocrine system and associated axes, especially as a reproductive toxicant through attenuation of the luteinizing hormone (LH). Current regulatory levels for chronic exposure are based on no observed adverse effect levels (NOAELs) of these LH alterations in rodent studies. Atrazine has also been studied for its effects on the central nervous system and neurotransmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…Here, we examined whether a model based on the nucleo-shuttling of the ATM protein is also relevant for the exposure to pesticide. To this aim, human skin fibroblast and brain astrocyte cells from different RIANS statuses were exposed to six current pesticides of domestic and environmental interest, namely gamma-hexachlorocyclohexane (lindane, HCH) [ 30 , 31 ], atrazine (ATR) [ 32 ], glyphosate (GBH) [ 33 ], permethrin (PER) [ 34 ], pentachlorophenol (PCP) [ 35 , 36 ], and thiabendazole (TBZ) [ 37 ] ( Table 1 ), and subjected to immunofluorescence, with the RIANS biomarkers as endpoints. The general objective of this paper is to better identify, document, and quantify the molecular steps of the individual response to pesticides that may lead to cellular death, whatever its form.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we examined whether a model based on the nucleo-shuttling of the ATM protein is also relevant for the exposure to pesticide. To this aim, human skin fibroblast and brain astrocyte cells from different RIANS statuses were exposed to six current pesticides of domestic and environmental interest, namely gamma-hexachlorocyclohexane (lindane, HCH) [ 30 , 31 ], atrazine (ATR) [ 32 ], glyphosate (GBH) [ 33 ], permethrin (PER) [ 34 ], pentachlorophenol (PCP) [ 35 , 36 ], and thiabendazole (TBZ) [ 37 ] ( Table 1 ), and subjected to immunofluorescence, with the RIANS biomarkers as endpoints. The general objective of this paper is to better identify, document, and quantify the molecular steps of the individual response to pesticides that may lead to cellular death, whatever its form.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that ATR is an endocrine disruptor causing disfunctions at normal human reproduction and development for both genders [ 16 ]. Furthermore, ATR was correlated to potential neurological and liver problems [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gonadal hormones are fundamental for the CNS’ activity during maturity and even senescence not only for their role in the neurogenesis processes, but also because they can exert a protective activity counteracting the insurgence of neurodegenerative disorders [ 14 ]. Moreover, EDC exposure may impact neurotransmitters also outside of the hypothalamus, which is known as a neuroendocrine structure [ 15 ]. Exposure to EDCs, as atrazine, may deregulate numerous pathways resulting in the multiple different health outcomes including neurotoxicity, which has been waived from inclusion in the most recent human health risk assessments [ 16 ].…”
Section: Introductionmentioning
confidence: 99%